Electrostatic Plasma Instabilities in Highly Active Aurora Observed by a Sounding Rocket S-310JA-7 - Ogawa, Tadahiko; Mori, Hirotaka; Miyazaki, Shigeru; Yamagishi, Hisao (1981)
P(論文) A sounding rocket S-310JA-7 launched from Syowa Station, Antarctica, carried into highly active auroras the Faraday cup for measuring electron density fluctuations of both 5-330Hz and 0.1-8kHz bands together with electron density and precipitating electron flux above 105eV. There existed two important irregular regions caused by electrostatic plasma instabilities. At altitudes of 100-140km both cross-field (gradient-drift) and two-stream instabilities were found, the excitation of which depends on the strength of DC electric field; the two-stream instability giving rise to high-frequency fluctuations becomes important when E≳25mV/m, while the cross-field instability exciting longer wavelengths is dominant when E≲25mV/m. Electrostatic ion cyclotron waves (frequency≃38-45Hz, frequency bandwidth≃10Hz) propagating nearly parallel to the auroral form were observed around a 200km altitude in association with strong field-aligned currents. Additionally, artificially modulated fluctuations due to the plasma wake produced by rocket body and other probes were detected. These results are discussed in the light of recent theories of electrostatic plasma instabilities in the auroral ionosphere. departmental bulletin paper